HELICOPTERS - Dittmer, Lori (Mankato, Minnesota : Creative Education and Creative Paperbacks, 2019)
A basic exploration of the parts, equipment, and variations of helicopters, the flying rescue vehicles. Also included is a pictorial diagram of the important rescue vehicle and its equipment.
Helicopter Beginnings High, Fast Fliers Hovering and Landing Air Ambulance Cockpit and Crew Helicopters at Work Amazing Helicopters Helicopter Blueprint.
Includes bibliographical references and index.
Keywords: Helicopters -- Juvenile literature; Helicopters in search and rescue operations -- Juvenile literature; Rescue work -- Juvenile literature